Eksplorasi Potensi Bacillus spp. sebagai Bakteri Pemacu Pertumbuhan Tanaman di Hutan Primer Resort Kembang Kuning - Anak Agung Putu Sidhiawan; Sukiman Sukiman; Sarkono Sarkono; Ernin Hidayati; Bambang Fajar Suryadi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Kembang Kuning resort is one of the Mount Rinjani National Park Resorts that have high biodiversity, so it has the potential for plant growth-promoting bacteria. Bacillus sp. is one species of bacteria that has great potential as a plant growth-promoting bacteria. The purpose of this study was to isolate and determine the ability of phosphate solubilization, nitrogen-fixing and anti-fungal activity of Bacillus spp. isolated from the Primary Forest of Kembang Kuning Resort, Gunung Rinjani National Park. This research is an exploratory study consisting of the isolation of Bacillus sp., phosphate solubilization test with spot inoculation method on Pikovskaya Agar media, qualitative nitrogen fixing test using Jensen's Nitrogen - Free media, and anti-fungal activity test against Fusarium sp. with dual culture method. There were 21 isolates of the genus Bacillus successfully isolated in this study. The phosphate solubilization test showed that 16 bacterial isolates could solubilize phosphate, where the highest phosphate solubilization index was produced by isolate P3.1 namely 0,52. A total of one isolate, namely isolate P3.1, can fix nitrogen on Jensen's Nitrogen-Free medium. In the anti-fungal test against Fusarium sp., three bacterial isolates were obtained that were able to inhibit the growth of Fusarium sp., where the highest antagonism was produced by isolate P2.8 which was 46,66%. Bacillus spp. isolated from Kembang Kuning Resort has potential as PGPB in terms of crop protection.